Identification of genetic markers of drug resistance based on whole genomes of clinical isolates of M.tuberculosis (Experimental biology, 2016)
Whole genome sequencing of 20 clinical isolated of M. tuberculosis using modern methods and instruments of next-generation sequencing. Most of the studied isolates (18) belong to Beijing family (Southern East Asian), with only two isolates were belong to T (Euro-American) and MANU-1 (Indo-Oceanic). The genetic markers for diagnostics of drug resistant forms of tuberculosis (MDR и XDR штаммы M.tuberculosis) were studied. The analysis of genetic loci of clinical isolates of M.tuberculosis that determine the resistance to TB drugs among found genomic variants, and corresponding genes. We found from 13 to 30 genetic loci with genomic variants among whole genome data of these 20 isolates of M.tuberculosis. We found that genomic variants in four genes coding proteins of РЕ/РРЕ family and which are unique and represented only by Mycobacterium species are very specific and found only in MDR and XDR strains of mycobacteria. Proteins of this family can play a significant role as virulence factors and may contribute to the successful infection.
Keywords: tuberculosis; Mycobacterium tuberculosis; DNA; whole genome sequencing; drug resistance; mutations.